2022
DOI: 10.1016/j.cjco.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes in Nova Scotia During the Early Phase of the COVID-19 Pandemic

Abstract: Background This study sought to determine the impact of the pandemic response to healthcare delivery on outcomes in patients with cardiovascular disease. Methods This is a population-based cohort study performed in the province of Nova Scotia (population 979,499), between Pre-COVID (March 1, 2017 – March 16, 2020) and in-COVID (March 17, 2020 – December 31, 2020) periods. Adult patients (≥18 years) with new onset or existing cardiovascular disease were included for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In Europe, data from Paris area [ 8 ▪ ] reported a 2-fold increase in OHCA incidence immediately before and during the weeks after Paris lockdown; similarly in England, both in London [ 9 ▪ ] and in North East England [ 10 ] where an increase in OHCA incidence strongly correlated with the daily number of COVID-19 cases was noticed in March–April 2020. Moving to America, an increase in OHCA during the first pandemic wave was pointed out not only in New York City, the most important USA outbreak of COVID-19 during the first wave, where a 3-fold increase in OHCA was highlighted [ 11 ▪ , 12 ], but in also in areas other than the United States of America [ 13 16 , 17 ▪▪ ], as in Canada [ 18 ] and in Brazil [ 19 ]. A slight increase was observed also in some areas in Asia, as in Singapore [ 20 ].…”
Section: Out-of-hospital Cardiac Arrest and Coronavirus Disease 2019mentioning
confidence: 99%
“…In Europe, data from Paris area [ 8 ▪ ] reported a 2-fold increase in OHCA incidence immediately before and during the weeks after Paris lockdown; similarly in England, both in London [ 9 ▪ ] and in North East England [ 10 ] where an increase in OHCA incidence strongly correlated with the daily number of COVID-19 cases was noticed in March–April 2020. Moving to America, an increase in OHCA during the first pandemic wave was pointed out not only in New York City, the most important USA outbreak of COVID-19 during the first wave, where a 3-fold increase in OHCA was highlighted [ 11 ▪ , 12 ], but in also in areas other than the United States of America [ 13 16 , 17 ▪▪ ], as in Canada [ 18 ] and in Brazil [ 19 ]. A slight increase was observed also in some areas in Asia, as in Singapore [ 20 ].…”
Section: Out-of-hospital Cardiac Arrest and Coronavirus Disease 2019mentioning
confidence: 99%
“…The global health crisis induced by coronavirus disease 2019 (COVID-19) has profoundly impacted the international community, public health systems, and economies [1][2][3]. Besides the impact on those infected, the pandemic has also had many indirect public health consequences, namely disruptions to routine care and health-seeking behaviours [4][5][6]. A decrease in survival for patients experiencing out-of-hospital cardiac arrest (OHCA) was observed [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] There are studies in other fields that have demonstrated worse presentation and outcomes of diseases that may have been improved with earlier intervention and assessment. 5,6 Renal colic, which affects approximately 12% of men and 6% of women, is one of the most common presentations to the ED. 7 Some studies have reported a decrease in the number of patients seeking urologic care, urology referrals, and similar or greater risk of admission during the early phase of the pandemic.…”
Section: Introductionmentioning
confidence: 99%